Expansion of Cross Necklace and Startail Fish Fins in Mechanically Stabilized Earth Walls On Red Soil Layer - Karminto, Karminto; Soegiarso, Roesdiman; Hamdhan, Indra Noer (Asian Journal of Social and Humanities, 2023)
Development in Indonesia is currently being actively carried out, especially development in the field of infrastructure, especially toll roads and bridges for opritnya, and due to development with limited Right Of Way (ROW) land, so that the oprit road body is not made slope with a certain slope, for that a construction that is not needed. For this reason, precast soil retaining walls are needed, generally precast soil retaining walls such as Mechanically Stabilized Earth Walls use geosynthetics that are not heat resistant and strip plates, where the interlocking strip plates between soils are less strong, in connection with this there are often failures of MSE Wall failures which are caused by these two factors and are influenced by hydrostatic water pressure and soil layers that are not suitable for construction take land left and right of the road. In connection with the above, it is necessary to have novelty Mechanically Stabilized Earth Walls with anchor strength where along the anchor there is a crossbar necklace and at the end there is a fish fin startail whose function is strong to resist shear and interlocking the ground is getting stronger.